Enhanced ethanol gas sensing properties of SnO2-Core/ZnO-Dhell Nanostructures - Thanihaichelvan, T.; Haseeb, A.S.M.A.; Akbar, S.A.; Sabri, M.F.M.; Hoong, W.Y. (sensors, 2014)
An inexpensive single-step carbon-assisted thermal evaporation method for the growth of SnO2-core/ZnO-shell nanostructures is described, and the ethanol sensing properties are presented. The structure and phases of the grown nanostructures are investigated by field-emission scanning electron microscopy (FESEM), transmission electron microscopy (TEM) and X-ray diffraction (XRD) techniques. XRD analysis indicates that the core-shell nanostructures have good crystallinity. At a lower growth duration of 15 min, only SnO2 nanowires with a rectangular cross-section are observed, while the ZnO shell is observed when the growth time is increased to 30 min. Core-shell hierarchical nanostructures are present for a growth time exceeding 60 min. The growth mechanism for SnO2-core/ZnO-shell nanowires and hierarchical nanostructures are also discussed. The sensitivity of the synthesized SnO2-core/ZnO-shell nanostructures towards ethanol sensing is investigated. Results show that the SnO2-core/ZnO-shell nanostructures deposited at 90 min exhibit enhanced sensitivity to ethanol. The sensitivity of SnO2-core/ZnO-shell nanostructures towards 20 ppm ethanol gas at 400 °C is about ~5-times that of SnO2 nanowires. This improvement in ethanol gas response is attributed to high active sensing sites and the synergistic effect of the encapsulation of SnO2 by ZnO nanostructures.
Keywords: ethanol gas sensor; hierarchical nanostructures; ZnO; SnO2